Antimicrobial Potential of Caffeic Acid against Staphylococcus aureus Clinical Strains. (15th July 2018) - Kępa, Małgorzata; Miklasińska-Majdanik, Maria; Wojtyczka, Robert D.; Idzik, Danuta; Korzeniowski, Konrad; Smoleń-Dzirba, Joanna; Wąsik, Tomasz J.
Abstract : Phenolic compounds constitute one of the most promising and ubiquitous groups with many biological activities. Synergistic interactions between natural phenolic compounds and antibiotics could offer a desired alternative approach to the therapies against multidrug-resistant bacteria. The objective of the presented study was to assess the antibacterial potential of caffeic acid (CA) alone and in antibiotic-phytochemical combination against Staphylococcus aureus reference and clinical strains isolated from infected wounds. The caffeic acid tested in the presented study showed diverse effects on S. aureus strains with the minimum inhibitory concentration (MIC) varied from 256 μ g/mL to 1024 μ g/mL. The supplementation of Mueller-Hinton agar (MHA) with 1/4 MIC of CA resulted in augmented antibacterial effect of erythromycin, clindamycin, and cefoxitin and to the lesser extent of vancomycin. The observed antimicrobial action of CA seemed to be rather strain than antibiotic dependent. Our data support the notion that CA alone exerts antibacterial activity against S. aureus clinical strains and has capacity to potentiate antimicrobial effect in combination with antibiotics. The synergy between CA and antibiotics demonstrates its potential as a novel antibacterial tool which could improve the treatment of intractable infections caused by multidrug-resistant strains.